Analisis Kompetensi Rekrutmen Pejabat Pemerintah Kabupaten Gorontalo - Junus, Dikson; Harun, Nur; Napir, Suaib; Nuna, Muten; Sari, Sumarti Puspa (Jurnal Pemerintahan dan Politik, 2024)
The appointment of civil servants in government structural positions is based on competence so that placement in government structural positions using the merit system considers aspects of qualifications, competence, and good performance. This research aims to analyze managerial, technical and socio-cultural competencies in the aspects of knowledge, skills, attitudes of officials who will be placed in the Gorontalo Regency government. The research approach uses qualitative methods, data collection is done through interviews, participatory observation, field notes, and document studies. Data analysis used an interactive model with three steps: condensing data, presenting data, and drawing conclusions or verification. Data condensation refers to the process of selecting, narrowing down, simplifying, summarizing, and transforming data. The findings in this research in the recruitment of Gorontalo Regency Government officials have referred to Law Number 5 of 2014, Regent Regulation Number 10 of 2017 which emphasizes aspects of technical competence, managerial competence and socio-cultural competence. In addition, the regulation also refers to the recruitment of officials who also pay attention to other aspects of competence such as integrity, cooperation, communication and skills. However, there are still interventions by groups of people who support candidates without regard to competence and educational background. Furthermore, in the mutation of structural officials in central and regional government agencies, although it has been carried out in accordance with statutory provisions, there is still political intervention. This research suggests that ASN must have adaptation competence or the ability to adjust to new or changing situations.